1996
DOI: 10.1074/jbc.271.23.13593
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the N and C Termini of Recombinant Neurospora Mitochondrial Porin in Channel Formation and Voltage-dependent Gating

Abstract: To investigate the role of the N and C termini in channel function and voltage-dependent gating of mitochondrial porin, we expressed wild-type and mutant porins from Neurospora crassa as His-tag fusion products in Escherichia coli. Large quantities of the proteins were purified by chromatography across a nickle-nitrilotriacetic acid-agarose column under denaturing conditions. The purified His-tagged wild-type protein could be functionally reconstituted in the presence of detergent and sterol and behaved in bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 42 publications
10
96
1
2
Order By: Relevance
“…Rather, the truncated proteins seem to adopt a conformation in the membrane that renders them more sensitive to proteolytic attack. In support of this hypothesis, we have observed that porin molecules lacking the N-terminus form unstable channels which rapidly fluctuate between numerous open substates [20].…”
Section: A269-283porinmentioning
confidence: 66%
See 2 more Smart Citations
“…Rather, the truncated proteins seem to adopt a conformation in the membrane that renders them more sensitive to proteolytic attack. In support of this hypothesis, we have observed that porin molecules lacking the N-terminus form unstable channels which rapidly fluctuate between numerous open substates [20].…”
Section: A269-283porinmentioning
confidence: 66%
“…The porin mutants used in this study were constructed as described previously [20] and cloned into the vector pGEM4 (Promega). Briefly, restriction fragments of the Neurospora porin cDNA clone [18] were replaced by PCR products lacking either amino acid residues 2-12 or 3-20, to create A2-12porin and A3-20porin, respectively (Fig.…”
Section: Construction Of Porin Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure represents an addition to the b-barrel pore structure and was proposed to have functionally relevant properties [20][21][22][23][24][25][26]35]. It has been recently proposed that the final N-terminal sequence (i.e.…”
Section: Role Of the Vdac N-terminusmentioning
confidence: 99%
“…The FLAG1, which is 11-20 residues from the N-terminus, will most likely have a trans exposure (see Fig. 1); especially if the Nterminus is as dynamic as proposed [8,13,[22][23][24][25]. Residues 1-10 continue through the lumen towards exposure of the extreme Nterminal residue to the cis side.…”
Section: Immunoprecipitation Of Intact and Disrupted Mitochondriamentioning
confidence: 99%